Social and legal problems of employment of the population of Ukraine during martial law - O. Tyshchenko; S. Chernous; D. Sirokha (Аналітично-порівняльне правознавство)
The article reveals the current trends in the Ukrainian labor market in the context of analyzing the issues of labor supply and demand in various spheres of labor activity. The author analyzes the impact of the COVID-19 pandemic on the effectiveness of the Decent Work Program for Ukraine for 2020-2024, initiated by the International Labor Organization to intensify reforms in the field of employment in Ukraine.